187 Mitochondrial Dysfunction in the Diabetic Heart â€" Imbalance in Fusion/Fission Axis?. (3rd June 2016) - Murfitt, Lucy; Monib, Mohammad M; Bennett, Hayley; Davenport, Bernard; Pinali, Christian; Cooper, Garth; Cartwright, Elizabeth; Kitmitto, Ashraf
Abstract : Background: Cardiovascular disease is the leading cause of morbidity and mortality among diabetic patients. Diabetic cardiomyopathy is closely linked to mitochondrial dysfunction, however the pathophysiological mechanisms responsible are not known. Maintenance of mitochondrial function relies on the balance between fusion and fission events. The fusion protein mitofusin-2 (Mfn2) has been implicated in the pathogenesis of diabetes. Alongside fusion, Mfn2 is widely believed to function as a molecular tether, binding mitochondria to the sarcoplasmic reticulum (SR) to form specialised Ca 2+ microdomains. Nonetheless, the role of Mfn2 in the heart is poorly characterised. Therefore, the aim of this study was to investigate changes to cardiac mitochondrial protein expression and function in diabetes with a particular focus upon the fusion/fission axis. Methods and results: Protein expression levels were measured in control and streptozotocin-treated (STZ) Wistar rat heart using Western Blot. Mitochondrial OXPHOS function was assessed using enzyme activity assays. Lastly, changes to the mitochondrial proteome were investigated using Mass Spectrometry (MS). Western Blot showed a significant increase in Mfn1 and Mfn2 expression levels in STZ compared to controls with no change to the fission protein Drp1. Enzymatic assays revealed that mitochondrial function was altered in the STZ rat heart compared to control. Lastly, MS identified 1437 proteins, of which there was an upregulation of proteins involved in beta oxidation in the STZ compared to controls. In contrast, there was a downregulation of proteins associated with OXPHOS in the STZ suggesting mitochondrial dysfunction that corroborates the functional data. Conclusion: These data suggest that mitochondrial dysfunction may be linked to an imbalance of the mitochondrial fusion/fission axis in the diabetic heart. Future work will focus on the 3-D reconstruction of the mitochondrial networks using electron microscopy to determine whether changes to mitochondrial function are linked to structural alterations. These studies will enhance our understanding of the pathogenesis of cardiac mitochondrial dysfunction in diabetes, with the hope to elucidate potential targets for therapeutic intervention.